Calcium channel blockade reduces mechanical strain-induced extracellular matrix gene response in lamina cribrosa cells. Issue 7 (20th March 2015) - Quill, B; Irnaten, M; Docherty, N G; McElnea, E M; Wallace, D M; Clark, A F; O'Brien, C J
Abstract : Purpose: This study examines the effect of the L-type calcium channel blocker verapamil on mechanical strain-induced extracellular matrix genes in optic nerve head lamina cribrosa (LC) cells. Methods: Changes in LC cell intracellular calcium [Ca 2+ ]i following hypotonic cell membrane stretch were measured with the fluorescent probe fura-2/AM. Fluorescence intensity was measured, after labelling, by calcium (Ca 2+ ) imaging confocal microscopy. Confluent human LC cell cultures were serum starved for 24 h prior to exposure to cyclical mechanical strain (1 Hz, 15%) for 24 h in the presence or absence of verapamil (10 mm). Transforming growth factor-β 1 (TGF-β1), collagen 6A3 (COL6A3) and chondroitin sulfate proteoglycan 2 (CSPG2) mRNA expression levels were assessed by quantitative RT-PCR. Results: Hypotonic cell membrane stretch of LC cells from normal donors significantly increased [Ca 2+ ]i (p<0.05). Exposure to cyclical mechanical strain (15% strain) produced a statistically significant increase in the three matrix genes that were examined (TGF-β1, COL6A3 and CSPG2). This response in both cyclical and mechanical stretch was significantly reduced by pretreating LC cells with the L-type calcium channel blocker verapamil (p<0.05). Conclusions: This study provides evidence of a novel mechanotransduction pathway linking mechanical strain, cation channel function and the induction of LC cell matrix gene transcription. This highlights the potential involvement of calcium influx in the activation of matrix remodelling responses in the optic nerve head and supports the rationale that calcium channel blockers may attenuate disease progression in glaucoma.